Size and sexual dimorphism in the most primitive birds, the palaeognaths - Bertelli, Sara Beatriz (2025)
Palaeognathae is the most divergent clade of extant birds (Neornithes). It includes several Gondwanan taxa, namely the tinamous, kiwis, emus, ostriches, cassowaries, and rheas, as well as recently extinct taxa such as the moas and elephant birds. Except for the tinamus, all other species are cursorial ratites that have lost the ability to fly. The group also include fossil genera such as Lithornis, Paleotis, and Diogenornis from the early Eocene (~55 million years ago). In this clade, body size ranges from extremely large birds – such as the extinct elephant birds Aepyornis maximus, with an estimated weight of 409 kg, and Vorombe titan, at 800 kg – to the dwarf tinamou Taoniscus nanus, weighing just 45 g. In this study, we reconstructed the evolution of body size in paleognath birds, with a focus on the diverse Tinamidae, using carefully curated body size data from extant and fossil taxa. To test previous hypotheses, and evaluate macroevolutionary patterns we applied comparative phylogenetic methods to estimate ancestral body sizes under different models of phenotypic evolution, and evaluated the evolution of female-biased sexual dimorphism of tinamous which is very variable in the group. Our results suggest that the ancestor of all extant palaeognaths weighed about 3 kg, and that gigantism evolved independently up to five times. Significant size reductions were observed in the ancestors of both forest-dwelling (Tinaminae) and steppe tinamous (Tinamotidinae). Preliminary interpretations indicate that size changed together in male and female tinamous, maintaining dimorphism throughout evolutionary time.